Вміст деяких мікроелементів у ґрунті та рослинах роду Pyrethrum Zinn. - Gurs'ka, O.V.; Pyda, S.V.; Hrigoryuk, I.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
It was found that plant of Pyrethrum parthenium (L.) Smith. and Pyrethrum coccineum (Willd.) Worosch., which are growing at a sufficiently secured microelements (Zn, Cu, Mn, Co, Ni, Pb, Cd) gray forest soil of Kremenets’ region, were accumulated significant amounts of Zn and Mn, low – Cu, Co, Ni, Pb and Cd.